Infiltration Between Popliteal Artery and Capsule of the Knee Combined with Adductor Canal Block as Analgesic Adjuvant During and Postoperative in Total Knee Replacement Surgery - David Rendra Mahardika; Tjokorda Gede Agung Senapathi; I Made Subagiartha (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Infiltration between the popliteal artery and capsule of the knee (iPACK) is one method that has been proposed in recent years as a potential alternative to peripheral nerve block as analgesia in total knee replacement (TKR) procedures. This study presents anesthetic management using spinal anesthesia combined with iPACK and adductor canal block (ACB) in patients with grade IV osteoarthritis who underwent TKR of the right knee. Case presentation: A woman, a housewife aged 50 years, was planning to undergo TKR surgery. The patient came with complaints of pain in the right knee 1 year before entering the hospital. The patient was given supplemental oxygen with a nasal cannula at 3 liters per minute. Prior to spinal anesthesia, the patient was given fentanyl 25 mcg iv, ketamine 10 mg iv, and midazolam 1.5 mg IV as premedication. The patient was positioned on the right side, and a 27G Quincke needle was inserted at the level of L3-L4 and given bupivacaine heavy 0.5% 7.5 mg, then lateralized for 15 minutes. After lateralization, the patient was positioned supine and used ultrasound to direct ACB action with a regimen of ropivacaine 0.25% + dexamethasone 5 mg a volume of 20 ml, then iPACK was performed with a regimen of Ropivacaine 0.375% + dexamethasone 5 mg a volume of 20 ml. After surgery, the patient is treated in the recovery room for 1 hour until bromage score is 0. The patient received the PCA Morphine analgesic demand only 1 mg/mL, 1 mg per dose, max 5 mg over 4 hours, lockout interval 6 minutes; Paracetamol 500 mg every 6 hours PO; Ibuprofen 400 mg every 8 hours PO. Conclusion: TKR patients who were given analgesia using the ACB peripheral nerve block technique combined with iPACK experienced a decrease in pain levels and lower use of postoperative morphine so that patient mobilization was faster and reduced the patient's length of stay.